2019
DOI: 10.3390/s19010148
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Modular Immunofiltration Columns for Frequency Mixing-Based Multiplex Magnetic Immunodetection

Abstract: For performing point-of-care molecular diagnostics, magnetic immunoassays constitute a promising alternative to established enzyme-linked immunosorbent assays (ELISA) because they are fast, robust and sensitive. Simultaneous detection of multiple biomolecular targets from one body fluid sample is desired. The aim of this work is to show that multiplex magnetic immunodetection based on magnetic frequency mixing by means of modular immunofiltration columns prepared for different targets is feasible. By calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This induced voltage is then amplified and filtered, and the amplitudes of the mixing terms can be determined. For example, in [36,38,43] this is done in a two-stage multiplication process, whereas in this work, we used direct digitalization of the signal trace and Fast Fourier Transform (FFT) analysis. This was chosen because we used different beads in this research, and different beads might create different phase shifts between the excitation and the detection signal traces, as shown in [44].…”
Section: Methodsmentioning
confidence: 99%
“…This induced voltage is then amplified and filtered, and the amplitudes of the mixing terms can be determined. For example, in [36,38,43] this is done in a two-stage multiplication process, whereas in this work, we used direct digitalization of the signal trace and Fast Fourier Transform (FFT) analysis. This was chosen because we used different beads in this research, and different beads might create different phase shifts between the excitation and the detection signal traces, as shown in [44].…”
Section: Methodsmentioning
confidence: 99%
“…The SignBit output of the driving frequency ( f 2 ) DDS, which changes its state when the most important bit of the internal DAC changes, is used for a triggered start of sample recording. In this research, we performed a direct digitization of the picked-up and preamplified signals, in contrast to prior work where a two-stage multiplication process was used [14,15,16,20]. This has the advantage that we can record many different harmonics at the same time and determine their phases without requiring a more complex hardware setup.…”
Section: Methodsmentioning
confidence: 99%
“…Different approaches have been performed both experimentally and in simulations to realize so-called multiparametric immunoassays [19]. Recently, we have shown a method where this is done by using the same MBs but with spatial separation of different capture zones [20]. When different types of MBs are used to label different targets, their different magnetic properties can be used to distinguish them without the need of spatial separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, a highly sensitive and quantitative detection of aflatoxin B1 has been demonstrated based on newly developed competitive magnetic immunodetection (cMID) [23]. Using frequency mixing magnetic detection (FMMD), a dose-depending measuring signal is obtained in a portable handheld measuring FMMD device [23,26,29,30]. A detailed explanation of FMMD is given in [23,29,31].…”
Section: Introductionmentioning
confidence: 99%